PROPORSI GANTI RUGI BAGI KORBAN ATAU KELUARGA KORBAN KECELAKAAN LALU LINTAS JALAN - Putri, Dhanastri Retnaning (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2023)
Transportation's role is essential as time progresses with quick mobility. It makes it possible for people to reach from one place to another. Ground transportation is one of the concise, easily found, and widely used modes.  As ground transportation traffic activity increases, it triggers an increase in traffic accidents. One of several factors that causes traffic accidents is human errors. The negligent aspect of human errors causes injury and the loss of life of other people. As a form of a sense of responsibility, the perpetrators of criminal accidents compensate the victim and family. This research uses normative juridical research methods by collecting data obtained through library research, namely by studying books, laws, regulations, websites, and other documents related to this research. The results obtained show that compensation is a form of legal protection for victims and a form of accountability for the perpetrators of criminal accidents. In addition, the amount of the proportion of compensation given to victims can be determined by several factors so that later it can be right on target and create justice for both parties.